Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah: Telaah terhadap Penyusunan KOM, Modul ajar, Modul Projek P5, dan PPRA - Sekarinasih, Anggitiyas; Waseso, Hendri Purbo (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2025)
This study aims to reveal the planning of the independent curriculum in elementary madrasas. The policy of implementing the independent curriculum in madrasas greatly determines the success of madrasas in forming a student-centered madrasa environment. Therefore, this study focuses on observing the preparation of madrasas in implementing the independent curriculum, compiling the operational curriculum of madrasas, compiling teaching modules, and compiling project modules for strengthening the profile of Pancasila students and the profile of rahmatan lil alamin students. This study was conducted qualitatively using data collection techniques such as interviews, observations, and documentation. The location of this study was MI Ma'arif NU Beji and MI Ma'arif NU Banjarparakan, with informants of the principal of the madrasa, class 1 teachers, and class 4 teachers. The results of the study showed that 1) the process of compiling the operational curriculum of madrasas is still not functional and is still interpreted as a document. KOM at MI Ma'arif NU Banjarparakan and MI Ma'arif NU Beji are still at the level of adopting the existing curriculum format; 2) the class 1 and class 4 teachers are still in the early stages of adapting existing teaching module examples; 3) the process of compiling project modules is still lacking in terms of understanding the concept of the project by teachers, resulting in minimalist project modules and some components are found to be lacking; 4) the obstacles faced by the madrasah arise due to the limited understanding of teachers so that further assistance and training are needed.